1984
DOI: 10.1149/1.2115248
|View full text |Cite
|
Sign up to set email alerts
|

Calcium / Ca ( AlCl4 ) 2 — Thionyl Chloride High Rate Cell

Abstract: The lithium-SO2 cell shows good performance over a wide range of temperatures and a good shelf life. In addition, it has the highest power density of all commercially available cells (1). For example, a C-size cell is capable of continuously delivering 1.5A at room temperature (2). However, because of hazard limitations, its recommended maximum continuous rate is only 0.36A (2). Recently, both the safety and rate capability of the Li-SO2 system were improved (3-5), and the recommended maximum continuous rate w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Staniewicz was the first to report on the electrochemistry of Ca–SOCl 2 as an alternative to the Li–SOCl 2 primary cells, again a battery technology mainly used for military applications, and presented the impossibility of calcium plating upon cell reversal as a safety advantage . Further studies by Peled et al attributed this feature to the formation of a passivation layer consisting mainly of CaCl 2 impermeable to the Ca 2+ ions. A similar technology with a somewhat higher operation cell potential was also developed, , but corrosion of the Ca metal electrodes was found to be an issue; the Ca–SOCl 2 cells lost ca. 10% of their capacity after only 2 weeks of storage .…”
Section: Introductionmentioning
confidence: 99%
“…Staniewicz was the first to report on the electrochemistry of Ca–SOCl 2 as an alternative to the Li–SOCl 2 primary cells, again a battery technology mainly used for military applications, and presented the impossibility of calcium plating upon cell reversal as a safety advantage . Further studies by Peled et al attributed this feature to the formation of a passivation layer consisting mainly of CaCl 2 impermeable to the Ca 2+ ions. A similar technology with a somewhat higher operation cell potential was also developed, , but corrosion of the Ca metal electrodes was found to be an issue; the Ca–SOCl 2 cells lost ca. 10% of their capacity after only 2 weeks of storage .…”
Section: Introductionmentioning
confidence: 99%
“…in limestone and gypsum, (2) its redox potential (close to Li/Li + ) and (3) its volume capacity, equal to the lithium one and (4) its markedly higher melting point (T m = 842 • C) when compared to alkaline metals and magnesium, it has been prioritized as a post-lithium technology. Indeed, Peled et al reported, roughly forty years ago, the high performance of a non-rechargeable calcium battery but also the cycling issues of calcium metal, Ca 0 [150,151]. Regarding safety hazards, all-solid-state batteries, ASSB, based on inorganic materials e.g.…”
Section: Statusmentioning
confidence: 99%
“…Therefore, it does not form Ca dendrite upon electrochemical plating/stripping reactions when being used as a battery material. Thionyl chloride [ 44 ] and intercalation cathodes [ 45 ] have been reported to couple with the Ca‐metal anode. However, the most challenging aspects in calcium batteries are the passivation of calcium anode [ 46 ] and the lack of reliable electrolytes.…”
Section: Nonaqueous Anode Chemistries Of LI Na Mg Al K and Camentioning
confidence: 99%